Medical uses of ozonized oils, an up-date (Ozone Therapy Global Journal, 2012)
Early evidence on the clinical use of ozonated oils first appear in scientific literature in1859. This paper reviews the general and main clinical applications of ozonated oilsthat have appeared in scientific literature between 1859-2011. The oxidation productsgenerated after the reaction of ozone with fatty acids and other substrates can acts asa germicide, immune stimulantand tissue restoration agent. The biological activitiesand stability of the ozonated oilsallows the development of standard formulations thatdeliver the benefits of ozone, supported by pre-clinical and clinical studies.The mainclinical studies that support t he u se of ozonized oils apply ozonizedsun flower oilorozonizedolive oil in different clinical conditions. The applications are essentially forexternal use, however there is evidence of immune-stimulating and repaireffects whenused orally. A deep study of the biological effects of various formulations already onthe mar ket will support the scientific b asis of the use of ozoniz ed o i l in differen tpathologies.